2007
DOI: 10.1093/nar/gkl1168
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation delays the ATF7 transcription factor subcellular localization and inhibits its transcriptional activity

Abstract: Over the past few years, small ubiquitin-like modifier (SUMO) modification has emerged as an important regulator of diverse pathways and activities including protein localization and transcriptional regulation. We identified a consensus sumoylation motif (IKEE), located within the N-terminal activation domain of the ATF7 transcription factor and thus investigated the role of this modification. ATF7 is a ubiquitously expressed transcription factor, homologous to ATF2, that binds to CRE elements within specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Sumoylation modulates the affinity with DNA binding and the activity of stem cell transcription factors (23), as well as the subcellular localization of general transcription factors (38,39). Our current study indicates that SALL4B sumoylation regulates its transcriptional activity.…”
Section: Discussionmentioning
confidence: 50%
“…Sumoylation modulates the affinity with DNA binding and the activity of stem cell transcription factors (23), as well as the subcellular localization of general transcription factors (38,39). Our current study indicates that SALL4B sumoylation regulates its transcriptional activity.…”
Section: Discussionmentioning
confidence: 50%
“…Another transcript potentially involved in the regulation of the two hotspots is the small ubiquitinlike modifier (SUMO). SUMO has emerged as an important regulator of diverse pathways and activities, including protein localization and transcriptional regulation (Hamard et al 2007), and was observed to interact with RAD23 (Ortolan et al 2000), an UV excision repair protein that is itself involved in chromatin-mediated repression of transcription, and is alleviated by both histone modifications and ATP-dependent chromatinremodeling activities (Gong et al 2006). Overall, these results exemplify how natural selection could act on a single master regulator controlling expression of a suite of numerous genes belonging to diverse functional groups in a tissue highly involved in the adaptive divergence of whitefish and that would be ultimately able to modulate notably the organism phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…The ATF7 derivatives were analyzed after their enrichment on Ni-NTA-agarose (ATF7 proteins are retained either via their zinc-finger or via their histidine-tagged SUMO-1 moiety) as previously described. 18 In the absence of activated p38β2, the phosphorylation of both Thr53 and Thr112 residues was observed (Fig. 3, lane 2).…”
Section: Phosphorylation Of the N-terminus Of Atf7mentioning
confidence: 92%
“…This latter region includes a critical zinc-binding element, two conserved threonine residues (T51 and T53 corresponding to the T69 and T71 homologues in ATF2), and also a lysine residue [unique to ATF7 (K118)] that is specifically targeted by the SUMO modification machinery. 17,18 The transcriptional activity of ATF7 and ATF2 is potentiated by the expression of TAF12, a subunit of TFIID, through direct interactions involving the N-terminal domain of the ATF protein and the TAF12 histone fold domain. 19 In the present study, we investigate the phosphorylation pattern of the ATF7 activation domain.…”
Section: Introductionmentioning
confidence: 99%